The effect of 17 methyltestosterone on sex reversal of the red tilapia, Oreochromis sp and its implication in tilapia production - Mohd Fariduddin Othman (Universiti Pertanian Malaysia, 2012)
17 methyltestosterone, administered orally to sexually undiffrentiated red tilapia fry, Oreochromis sp., at a dose of 30 and 60 ug gm of feed and over a 20 and 30 day treatment period successfully produced a 82 - 95% male population